2020
DOI: 10.15244/pjoes/111230
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Environmental Investment on Financial Performance: Evidence from Chinese listed Companies

Abstract: Using the data of Chinese listed companies during 2012-2016, this study examines the effect of environmental investment on financial performance, as measured by return on assets (ROA). We also examine the moderating effect of industry attributes, company ownership, and region on this relationship. The empirical results show that there exists a U-shaped relationship between environmental investment and financial performance. However, only 11% of Chinese listed companies can attain profitable environmental inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 35 publications
(49 reference statements)
0
16
0
Order By: Relevance
“…Moreover, higher environmental performance may diametrically elicit prominent financial performance. Jian Xu et al claim the correlation between environmental investment and financial performance can be illustrated by a virtually U-shaped curve, which elucidates that investing more in greenness can give rise to better financial performance and vice versa [8]. On the basis of 243 firms utilizing independently developed environmental ratings, Russo and Fouts established a model grounded on the resource-based view of firms, corroborating high levels of environmental performance corresponding to enhanced profitability.…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…Moreover, higher environmental performance may diametrically elicit prominent financial performance. Jian Xu et al claim the correlation between environmental investment and financial performance can be illustrated by a virtually U-shaped curve, which elucidates that investing more in greenness can give rise to better financial performance and vice versa [8]. On the basis of 243 firms utilizing independently developed environmental ratings, Russo and Fouts established a model grounded on the resource-based view of firms, corroborating high levels of environmental performance corresponding to enhanced profitability.…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…Further, the understanding of a non-linear association amongst environmental and economic practices emerged with Barnett and Salomon (2012), who argued that, "as the firm upsurges environmental performance, at initial FP declines, but subsequently rebounds as the environmental performance rises with more critical resources and better management discretion in the long run." Similarly, researchers like Hart (1995); Russo and Fouts (1997); Jin and Xu (2020) In the empirical model of the study, four firm-specific parameters are taken as the control variables with the motto of improving the correctness of forecasts and the dependability of the inference from the analysis. These parameters are frequently used in earlier studies like company size, board size, firm age, debt-equity ratio (DER) (Al-Tuwaijri et al, 2004).…”
Section: Evidence For a Relationship-positive Negative Or Nonlinearmentioning
confidence: 99%
“…Based on the environmental perspective, Guenster et al (2011) found that corporate environmental protection expenditure has no significant impact on financial performance, whether positive or negative. In addition, some researchers have proposed that there is a U-shaped curve relationship between enterprise environmental protection expenditure and financial performance (Jin and Xu 2020). Some literatures analyze the impact of environmental protection expenditure on the later financial performance of enterprises from a cross period perspective.…”
Section: Environmental Protection Expenditure and Financial Performan...mentioning
confidence: 99%